Perbedaan Waktu Hauling Bagan Tancap terhadap Hasil Tangkapan di Perairan Sungsang, Sumatera Selatan - Fauziyah Fauziyah; Freddy Supriyadi; Khairul Saleh; Hadi Hadi (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2013)
Anchovies (Stolephorus sp.) were the target species of stationary lift nets in Sungsang estuary of South Sumatra including others small pelagics. Fishermen of stationary lift net in Sungsang estuary operated before midnight until early morning. In order to obtain optimum catches, it was necessary to know when the right time to operate the stationary lift nets. The research objectives were 1) to analyze the effect of hauling time on the catch, and 2) to determine the optimum hauling time of stationary lift net in Sungsang estuary. The research was conducted in May 2012 with Experimental Fishing methods and completely random design models with treatment differences in hauling time was before midnight (21:00 to 23:59), around midnight (00:00 to 02:59), and after midnight (03:00 to 5:59). The fourth stationary lift net was operated for 3 days (3 trips). All data were processed using SPSS 17 software for windows. The results indicated that the hauling time significantly affected the catch and the optimum hauling time of stationary lift net in Sungsang estuary was around midnight (00:00 to 02:59).